Impacts of ventilation: studies on “before and after” a smoking ban is implemented - Geens, Andrew; Snelson, David; Al-Madfai, Hasan; Hillier, David (Journal of Environmental Engineering and Landscape Management, 2011)
A number of legislative bodies in Europe have already made or are currently considering making policy decisions on the issue of smoking in public places. Policy alternatives have been discussed in Town and Country Planning (2002). In the last decade, the scientific evidence relating to this debate has been reported in a diverse range of publications such as the British Medical Journal, Indoor Air and The Chartered Institution of Building Services Engineers journal. On inspection much of this reporting concludes negatively on the performance of ventilation systems. In this paper, a critical review is undertaken of the “before and after smoking ban” study papers. This paper aims to critically review the findings of these studies in relation to ventilation and draw some working conclusions from these studies.Article in English.Vėdinimo poveikis: tyrimai prieš įvedant ir įvedus rūkymo draudimą Santrauka. Daug teisinių institucijų Europoje jau padarė ryžtingus sprendimus rūkymo viešose vietose klausimais ar dar svarsto dėl jų priėmimo. Apie alternatyvas buvo diskutuojama Town & Country. Būta įvairių publikacijų, susijusių su šiomis diskusijomis, pateikta mokslinių įrodymų, pavyzdžiui, Didžiosios Britanijos Medical Journal, Chartered Institution of Building Services Engineers leidiniuose. Daug išvadų siejasi su negatyviu ventiliacijos sistemų veikimo vertinimu. Apžvalga atliekama ištyrus situaciją prieš įvedant rūkymo draudimą ir jį įvedus. Siekta peržiūrėti tyrimų, susijusių su vėdinimu, išvadas ir padaryti tam tikrus sprendimus.Reikšminiai žodžiai: vėdinimo sistemos, tabako dūmai, rūkimo draudimas, cigaretės, teisės aktai.Воздействие вентиляции: исследование до и после запрета на курениеРезюме. Многие правовые институции в Европе уже приняли решения или рассматривают возможность принятия реше- ний, касающихся вопроса о курении в общественных местах. Дискуссия о возможных альтернативах велась в Town & Country. Дискуссиям на эту тему было посвящено немало публикаций, представлены научные доказательства, например, в издаваемых в Великобритании журналах Medical Journal, Chartered Institution of Building Services Engineers. Во многих выводах приводится негативная оценка действия систем вентиляции. Приводимый в статье анализ основан на исследовании ситуации до введения запрета на курение и после его введения. Предпринята попытка оценить выводы исследований, касающихся действия систем вентиляции, и предложить определенные решения.Ключевые слова: системы вентиляции, табачный дым, запрет на курение, сигареты, правовые акты.